Crop Management Practices in Rural Riverine Islands of Bangladesh - Aliyu Akilu Barau; Md Safiul Islam Afrad; Abdul Halim; GKM Mustafizur Rahman; Md Enamul Haque (Pattimura University Ambon Maluku Indonesia, 2021)
This study focused on farmers’ crop management practices in selected rural riverine islands (Char lands) of Sariakandi Upazila, Bogura district, Bangladesh. Disproportionate stratified sampling was adopted to select the respondents. The data were elicited using an interview schedule and analyzed via Statistics 10 software. Results revealed that, on average, there was moderate knowledge on crop management practices, and the attitude towards the practices was favorable. But, in deviance from what is habitually obtained on mainland Bangladesh where rice cultivation dominates, jute (35.84%) and chili (28.4%) covered the majority in Char Ghagua and Char Shaluka, respectively. In Char Tengrakura, rice and chili covered a little above half (52.7%) of the crops cultivated by the respondents. In terms of the management practices, the lion’s share (81.7%, 74.7%, and 77.0%) of soil management practices was covered by chemical fertilizers in all the Char lands. Similarly, the use of chemicals dominated when handling pests and diseases. Triple cropping was foremost across the Char lands and had high mean coverage in Char Tengrakura (63.6%). The mean coverage of irrigation water management practices was virtually shallow tube well in the Char lands. Generally, there was moderate knowledge and a positive attitude towards crop management practices. That crop management practices (use synthetic materials and underground water) employed in the Char lands are unsustainable, tending to induce degradation of land and water resources.